Manfaat Digital Payment Sebagai Alat Pembayaran Bagi UMKM Pada Sekolah Menengah Atas Negeri 5 Kabupaten Kepahiang - Sulisti Afriani; Herlin Herlin; Sri Handayani; Kiemas Kurniawan TA (Jurnal Dehasen Mengabdi, 2026)
Indonesian MSMEs contributed more than 61% of Indonesia's GDP in 2024, valued at IDR 9,580 trillion, and play a crucial role in Indonesia's economic growth. MSMEs (Micro, Small, and Medium Enterprises) in Indonesia have yet to fully digitize. Of the more than 66 million MSMEs, only 24 million have digitized. The government continues to encourage MSME growth towards digitalization, so that quality local products and small businesses become widely known by leveraging technology, social media, and digital payments. MSMEs must be bold in adapting and innovating regarding MSME digitization. Furthermore, financial technology (fintech) institutions can play a role in encouraging the widespread implementation of MSME digitization. Fintech companies and banks have made numerous breakthroughs in payment technology for businesses. Digital payments have become an integral part of small business development in Indonesia. As more consumers shift to cashless payment methods, this can encourage MSMEs to adopt digital payment technology and experience various benefits for MSMEs in penetrating the competitive landscape. Digital payments have become one of the most significant technological innovations in recent years. For Micro, Small, and Medium Enterprises (MSMEs), digital payments can be an effective payment tool to increase efficiency, security, and customer satisfaction. This study aims to identify the benefits of digital payments as a payment tool for MSMEs. (https://www.risetkita.id/manfaat-pembayaran-digital-bagi-umkm/) .